The shocking world of electricity with Max Axiom, super scientist - O' Donnell, Liam author; Dominguez, Richard illustrator; Barnett, Charles illustrator (London : Raintree, 2008)
Graphic science demonstrates and explains science. Whether shrinking down to the size of an ant or riding on a sound wave, it makes science a lot more accessible, by explaining science concepts and reinforcing scientific knowledge.